Konstitusionalitas Penerapan Hukum Adat dalam Penyelesaian Perkara Pidana - Danil, Elwi (Jurnal Konstitusi, 2012)
Indonesia is a plural country with a lot of diversities in it. As a country that embracing positivistic in law perspective, Indonesia is applying the codification of law that has most popular maxim: the certainty of law. That maxim can reduce traditional law that believed by indigenous people. This paper talks about possibility of criminal law in traditional law perspective in Indonesian plural culture.